Lithoselatium tantichodoki, a new species of intertidal crab (Crustacea:Brachyura: Sesarmidae) from southern Thailand - Promdam, Rueangrit; Ng, Peter K. L. (Zootaxa, 2009)
A new species of intertidal sesarmid crab, Lithoselatium tantichodoki new species, is described from the Gulf of Thailand. The species is superficially similar to L. kusu Schubart, Liu & Ng, 2009, from Singapore and Malaysia, but differs in the proportions of the ambulatory legs and the structure of the male first gonopod.